Training total laparoscopic gastropexy using a composed simulator and evaluating the significant transfer of surgical skills performed in growing pigs in vivo - Carlos A. Oviedo-Peñata; Juan D. Lemos-Duque; Juan G. Maldonado-Estrada (BMC Veterinary Research, 2025)
Abstract Background An advanced curriculum for training Total Laparoscopic Gastropexy (TLG) was developed using the CVLTS-composed simulator based on an ergonomic model of a canine abdominal cavity. The performance of Veterinary surgeons trained in basic laparoscopic surgical skills during 15 training TLG sessions (experimental group, n = 10) was compared to the TLG performance of veterinary surgeons with intermediate (n = 10) or advanced (n = 6) laparoscopic skills. The transfer of surgical skills to a live model was assessed by performing TLG in fattening pigs under operating room conditions using barbed sutures. Experimental group performance after accomplishing the TLG training curriculum and all groups’ performance during TLG in the in vivo model were videotaped and evaluated by external Minimally Invasive Surgery (MIS) experts using the GOALS and TLG-specific ranking (SRS) scales. Also, a quantitative assessment comprising time, smoothness of movements, and angular displacement using a Hand Movement Assessment System (HMAS) was performed. Besides, a postmortem biopsy recovered from the gastropexy site three months after surgery to evaluate gross and microscopic characteristics by histopathology was analyzed. Results GOALS and SRS scores (P < 0.05), and time, smoothness of movements, and angular displacement during TLG (P < 0.01) significantly improved in the Experimental group after training. They also compared their performance with expert and intermediate groups (P < 0.05) performances. The learning curve for intracorporeal suture stabilized since the tenth (out of 15) training session. Besides, trainees achieved significant TLG skills’ in vivo transfer, with no significant difference from the intermediate and expert group performances. The presence of mature collagen (100% of cases), cartilage and bone metaplasia, and foreign body reaction (25% of cases) were found at histopathology evaluation of the gastropexy site, evidencing normal healing. Conclusion The TLG training curriculum supported the acquisition of TLG surgical skills in the training box and their transfer to the in vivo model. The experimental group’s TLG performance in vivo did not significantly differ from the intermediate and expert groups. The clinical outcome and histopathological findings evidenced complete gastropexy-site healing.